Does Sexual Orientation Sell? : A Study of Homosexuality in Advertising - Schug, Laurena (My University, 2015)
This project looks at consumers? thoughts on advertising by incorporating characteristics of diversity within advertisements.
Color poster with text, photographs, and bar graphs.
Keywords: LGBT; Sexual orientation; Advertising; Posters